2020
DOI: 10.1128/msystems.00412-20
|View full text |Cite
|
Sign up to set email alerts
|

Shifts in the Bacterial Population and Ecosystem Functions in Response to Vegetation in the Yellow River Delta Wetlands

Abstract: Vegetation represents probably the most crucial step for the ecosystem functions of wetlands, but it is unclear how microbial populations and functions shift along with vegetation. In this study, we found that the richness and diversity of soil bacteria increased with vegetation levels and that the community composition was distinctly shifted from bare to vegetative places. The bare land displayed an extremely high abundance of Cyanobacteria as a monospecies genus, while a Gemmatimonadetes genus was predominan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 61 publications
2
13
0
Order By: Relevance
“…It has been previously noted that Euryarchaeota , a phylum containing methanogens, dominates wet ecosystems whereas Thaumarchaeota , a phylum containing ammonia oxidizers, dominates in drier systems [ 40 ]. Our finding that Gemmatimonadetes is a possible indicator of wetland development was supported by [ 41 ], which found Gemmatimonadetes in vegetated, but not bare wetlands. Actinobacteria and Bacteroidia , which were consistently less dominant in natural sites compared with the other treatments, may be indicators of disturbance or early succession, as noted by [ 42 ].…”
Section: Discussionsupporting
confidence: 84%
“…It has been previously noted that Euryarchaeota , a phylum containing methanogens, dominates wet ecosystems whereas Thaumarchaeota , a phylum containing ammonia oxidizers, dominates in drier systems [ 40 ]. Our finding that Gemmatimonadetes is a possible indicator of wetland development was supported by [ 41 ], which found Gemmatimonadetes in vegetated, but not bare wetlands. Actinobacteria and Bacteroidia , which were consistently less dominant in natural sites compared with the other treatments, may be indicators of disturbance or early succession, as noted by [ 42 ].…”
Section: Discussionsupporting
confidence: 84%
“…Some likely sources of ARGs in Kuwait's marine environment could be the chronic metal discharges from the shipping industry, desalination plants, and airborne input with dust, in addition to the pharmaceuticals introduced through wastewater discharges. The AMR is also reported in the Yellow River Delta [54], Yangtze river basin [55], Karst River [56], Xisha Island [49], and Ili River [57]. Proteobacteria (46%), Bacteroidetes (10%), and Actinobacteria (5%) were the main hosts of ARGs in the Kuwait coastal area.…”
Section: Discussionmentioning
confidence: 75%
“…Studies of the plant rhizosphere micro-organisms in the Yellow River Delta have attracted a great deal of attention. Our previous studies have reported the shifts of bacterial populations and ecosystematic functions in response to vegetation in the Yellow River Delta wetlands [19] and proposed a novel species of Psychroflexus aurantiacus in the family Flavobacteriaceae (strain YR1-1 T ) [20]. As an extreme habitat, saline-alkali soil contains a large number of microbial resources, which may have physiological and biochemical characteristics, with potential usefulness.…”
Section: Habitat and Cultivationmentioning
confidence: 99%